Multi-criteria performance analysis of dual miller cycle-Organic rankine cycle combined power plant - Zerom, Merhawi Samuel; Gonca, Guven (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Performance improvement in power generation systems have been current issues in the recent years. Combined power plants including Organic Rankine Cycle are promising for performance improvement to generate efficient energy. This study has examined a way of optimum conditions for both efficiency and exhaust emissions by introducing a combined plant of Dual Miller Cycle-Organic Rankine Cycle focused on diesel engine applications. Three different types of working fluids with appropriate characters are used in the Organic Rankine Cycle. Effective efficiency, effective power, exergy destruction, effective power density, ecological coefficient of performance, exergetic efficiency and effective ecological power density are investigated for both Dual Miller Cycle and Dual Miller Cycle - Organic Rankine Cycle combined plant configurations. The impacts of engine design and working parameters such as cycle temperature ratio, cycle pressure ratio, engine speed, cylinder dimensions and equivalence ratio on the performance parameters are investigated. Octafluorocyclobutane and pentafluoropropane have been used as working fluids of Organic Rankine Cycle. The results showed that pentafluoropropane is the best suitable organic fluid. The effective efficiency, ecological coefficient of performance and exergy destruction have been found as 45.42%, 74.14% and 12.4 kW, respectively. The results of this examination have shown optimum values of the engine design and operating parameters in terms of thermoecological feasibility which also reduces harmful ship emissions like nitrous oxides.
Keywords: Dual Miller Cycle; Organic Rankine Cycle; Optimization; Diesel engine; Emission; ENGINE; TURBINE; DESIGN; MODEL; Thermodynamics; Energy & Fuels; Mechanics